2003
DOI: 10.1038/sj.bjp.0705519
|View full text |Cite
|
Sign up to set email alerts
|

Pentobarbitone modulates calcium transients in axons and synaptic boutons of hippocampal CA1 neurons

Abstract: 1 Although barbiturates, like other general anaesthetics, depress excitatory synaptic transmission in the central nervous system (CNS), the underlying cellular mechanisms remain unresolved. They may increase the likelihood that an action potential will fail to invade every branch of the axonal arbour, thereby decreasing the synaptic drive to the postsynaptic neurons. Alternatively, they may inhibit calcium entry into the presynaptic terminals, thus reducing transmitter release. 2 To resolve these issues, we ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…CNS depression arises from their well‐known enhancement of inhibitory post‐synaptic Cl ‐ currents carried by GABA A receptors (Evans, 1979; Mathers and Barker, 1980; Olsen, 1988; Macdonald et al . 1989), and also by inhibition of excitatory pre‐synaptic neurotransmitter release (Brooks and Eckert, 1947; Weakly, 1969; Richards, 1972; Baudoux et al ., 2003) involving reduced Ca 2+ entry into the pre‐synaptic nerve terminal (Morgan and Bryant, 1977; Leslie et al . 1980; Baudoux et al ., 2003).…”
Section: Introductionmentioning
confidence: 99%
“…CNS depression arises from their well‐known enhancement of inhibitory post‐synaptic Cl ‐ currents carried by GABA A receptors (Evans, 1979; Mathers and Barker, 1980; Olsen, 1988; Macdonald et al . 1989), and also by inhibition of excitatory pre‐synaptic neurotransmitter release (Brooks and Eckert, 1947; Weakly, 1969; Richards, 1972; Baudoux et al ., 2003) involving reduced Ca 2+ entry into the pre‐synaptic nerve terminal (Morgan and Bryant, 1977; Leslie et al . 1980; Baudoux et al ., 2003).…”
Section: Introductionmentioning
confidence: 99%
“…pre increase in the presynaptic boutons [16,17] and depresses excitatory synaptic transmission in the CNS [18]. In these reports, the inhibitory [13,14] and 150-300 lM [17,18], respectively. Pentobarbital concentration of 200 lM was sufficient to inhibit depolarization-induced secretion by 30-50% [18].…”
Section: Discussionmentioning
confidence: 94%
“…-evoked glutamate release from rat cerebrocortical slices by mediating activation of GABA A receptors [13]. However, it has also been suggested that presynaptic GABA A receptors are not implicated in depressant actions of IV anesthetic agents in the presynaptic boutons [16,17]. Furthermore, it has been reported that GABA A receptors also reduce neurotransmitter release by another mechanism that does not affect Ca 2?…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Thus, pentobarbital depressed EPSP responses by both enhancing dendritic inhibition, as well as by a presynaptic action to reduce glutamate release as previously reported. (36) …”
Section: Resultsmentioning
confidence: 99%